#### Answer

$g(-19)=-3$

#### Work Step by Step

$g(x)=\sqrt[3] {x-8}$
$g(-19)=\sqrt[3] {-19-8}$
$g(-19)=\sqrt[3] {-27}$
$g(-19)=-3$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$g(-19)=-3$

$g(x)=\sqrt[3] {x-8}$
$g(-19)=\sqrt[3] {-19-8}$
$g(-19)=\sqrt[3] {-27}$
$g(-19)=-3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.